Cladistic analysis of the Stephaniellaceae (Marchantiophyta) based on morphological data. Issue 1 (2nd January 2016) - JuÁrez-martÍnez, Catalina; Ochoterena, Helga; Delgadillo-moya, Claudio
Abstract : This work evaluates the phylogenetic relationships between Stephaniellaceae, Arnelliaceae, Southbyaceae, and Gymnomitriaceae, and between genera and species of the Stephaniellaceae. We analysed morphological data obtained from herbarium specimens and from the literature under the parsimony criterion using equal weightings and implied weightings. The inclusion of Stephaniella and Stephaniellidium within Arnelliaceae, Southbyaceae or Gymnomitriaceae is not supported in this analysis. The clade Stephaniellaceae had a moderately high Jackknife support and the family was characterized by the following synapomorphies: presence of paraphyllia and presence of longitudinal folds in female bracts. Within the Stephaniellaceae, Stephaniella is corroborated as monophyletic and Stephaniellidium is resolved as its sister group. The relationship between Stephaniella uncifolia Winkler and Stephaniella hamata Stephani was strongly supported in both analyses while the relationship between Stephaniella paraphyllina Jack and Stephaniella boliviensis Stephani was weakly supported. With these results, S. boliviensis is proposed as a synonym of S. paraphyllina. We propose changes in the taxonomic position of Stephaniella and Stephaniellidium and in their classification in consideration of the complex morphology of the species and the lack of sexual structures and collections.